Checklist and context-bound evaluations of online learning in higher education - Hosie, Peter; Schibeci, R. (Blackwell, 2005)
A review is undertaken of what different commentators have written about the evaluation of educational courseware in higher education. Speculation is made on the reasons for the lack of such evaluations. The role of checklists for evaluating online courseware is discussed despite the acknowledged limitations. Checklists have been developed at Edith Cowan University specifically for assessing aspects of online pedagogical learning materials in higher education. These checklists are intended to be useful indicators of the areas where online learning materials are strong and identify areas that may be deficient rather than to arrive at a numeric score. The form of checklist proposed is a valuable screening device to use before undertaking a context-bound evaluation of courseware.Contextual evaluations are a complementary and valuable alternative to traditional forms of evaluation of educational courseware, such as checklists. A case is also made in this article for using a checklist developed for assessing aspects of online pedagogical learning materials in higher education. It is argued that, when used in conjunction with a context-bound approach, such checklists may be more useful in indicating the pedagogical quality of online learning materials.Quality of the instructional design remains an important consideration in evaluating courseware. Continuing comments and dissent are invited on the value of contextual evaluations of educational courseware to reinvigorate the debate over appropriate ways of evaluating online courseware that will provide helpful information for higher education.